A very rare case of adenomatoid hyperplasia of minor salivary gland in a 55 year old male patient - Eunice Johannas, Rokkala; Kadiri, Sailatha; Sameera, P R S S; Sri Vidhya, Tammina Mohana; Murali Mohan, K V (Indian Journal of Case Reports, 2024)
Adenomatoid hyperplasia of minor salivary glands (AHMSG) is an extremely rare non-neoplastic enlargement of minor salivary glands with uncertain pathogenesis. It is most commonly seen in males around 40–50 years of age. The most common sites are hard or soft palate. Clinically, the lesion presents as a sessile tumor-like nodule which mimics neoplasm with histological findings of benign hyperplasia and hypertrophy of mucous glands. Herein, we report a very rare case of AHMSG in a 55-year-old male patient who presented with asymptomatic swelling over the floor of the mouth since 8 months.